Risk of tuberculosis among Alabama children and adolescents treated with tumor necrosis factor inhibitors: a retrospective study - Matthew L. Stoll; James Aaron Grubbs; Timothy Beukelman; Melissa L. Mannion; Traci W. Jester; Randy Q. Cron; Marilyn J. Crain (BMC, 2017)
Abstract Background Tumor Necrosis Factor inhibitors (TNFi) have dramatically improved the outlook for patients with inflammatory arthritides and bowel disease (IBD), but are associated with increased infection risks, including tuberculosis (TB). Pediatric inflammatory diseases are uncommon, and the risk of TB in children taking TNFi remains unclear. The objective of this study was to report the incidence of TB disease among TNFi recipients at a single pediatric medical center serving most of Alabama compared to that of the general population of Alabama children. Methods Instances of TNFi usage among patients under age 20 years from July 1, 2007 through April 17, 2015 were captured from electronic health records at Children's of Alabama (CoA), which has the only pediatric rheumatology clinic in Alabama, and where a substantial number of children in Alabama with inflammatory bowel disease receive care., and reports of TB cases were obtained from the Alabama Department of Public Health (ADPH). Incidence was expressed as TB cases/10,000 person-years, using population estimates from the Alabama Center for Health Statistics. Results 1033 Alabama patients at CoA who were residents of Alabama were identified who received TNFi for a total of 1564 person-years. One adolescent on TNFi developed severe extrapulmonary TB (incidence density = 6.4 per 10,000; 95% CI 0.9-45.4 per 10,000). Sixty-three cases occurred in persons not on TNFi (incidence density = 0.064 per 10,000; 95% CI 0.050-0.082 per 10,000). Conclusions One case of TB disease among TNFi-exposed children was identified for 1564 person-years in Alabama residents. Although rare, this is higher than expected relative to the general rate of TB in Alabama. Thus, continued diagnostic vigilance for TB in children taking TNFi is required. Trial registration number Not applicable.